Handover Parameters Optimisation Techniques in 5G Networks - Wasan Kadhim Saad; Ibraheem Shayea; Bashar J. Hamza; Yousef Ibrahim Daradkeh; Waheb A. Jabbar; Hafizal Mohamad (Multidisciplinary Digital Publishing Institute, 2024)
Sensors 2021, 21(15), 5202; https://doi.org/10.3390/s21155202